Transformation of Consumer Protection Against Loss of Customer Funds in Digital Banking - Azis, Miftakul; Santiago, Faisal (Journal of Comprehensive Science, 2024)
Digital banking has become a major trend in the global financial sector, offering ease of access and efficiency for customers. However, this development also brings new risks, particularly related to the loss of funds due to cyber attacks. This research analyzes the legal vacuum in the regulations protecting customers of digital banking in Indonesia, particularly as regulated by POJK No. 12/POJK.03/2021 and POJK No. 13/POJK.03/2021. Despite the existing legal framework, this study identifies the weak legal protection for customers regarding the risk of losing funds due to cyber attacks, as well as the lack of clarity regarding the bank's responsibility in such situations. By examining national and international case studies and providing recommendations for regulatory enhancement and security standards, this study aims to contribute to the ongoing efforts to protect consumers in the increasingly complex context of digital banking.